2008
DOI: 10.1016/j.molcata.2008.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced degradation of 2,4-dinitrotoluene by ozonation in the presence of manganese(II) and oxalic acid

Abstract: a b s t r a c tManganese catalytic ozonation of 2,4-dinitrotoluene (DNT) in the presence of oxalic acid was studied. The addition of manganese ion (Mn 2+ ) or oxalic acid alone in ozonation process did not enhance DNT degradation, but the addition of Mn 2+ coupled with oxalic acid accelerated degradation of DNT. The DNT degradation efficiency was influenced by carbonate in the catalytic ozonation process. Kinetics study showed that Mn 2+ catalytic ozonation significantly promoted the decomposition of ozone. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The presence of carbonate/bicarbonate ions resulted in the lowest percentage of MB removal. It has been reported that that bicarbonate and carbonate ions are a radical scav- engers [45] that can trap hydroxyl radicals generated at the surface of the Co-BiVO 4 . As the concentration of reactive radicals decreased the percentage of photocatalytic decoloration was decreased.…”
Section: Effect Of Supporting Electrolytementioning
confidence: 99%
“…The presence of carbonate/bicarbonate ions resulted in the lowest percentage of MB removal. It has been reported that that bicarbonate and carbonate ions are a radical scav- engers [45] that can trap hydroxyl radicals generated at the surface of the Co-BiVO 4 . As the concentration of reactive radicals decreased the percentage of photocatalytic decoloration was decreased.…”
Section: Effect Of Supporting Electrolytementioning
confidence: 99%
“…Therefore, hydroxyl groups on the Mn-Cu-O catalyst surface played an important role in HCOP system. The addition of NaH 2 PO 4 in the HCOP system allowed us to evaluate whether the hydroxyl groups on the catalyst were active sites for ozone decomposition into hydroxyl radicals Xiao et al 2008); (Zhao et al 2013. NaH 2 PO 4 can strongly bind with the surface hydroxyl group of the catalyst .…”
Section: Catalytic Mechanismmentioning
confidence: 99%
“…In recent years, various technologies have been developed for environmental pollutants removal [1]. In general, the treatment of dye-containing effluents is being undertaken by biological [2], adsorption [3], membrane [4], coagulation-flocculation [5], oxidation-ozonation [6] and advanced oxidation processes (AOPs) [7].…”
Section: Introductionmentioning
confidence: 99%